ANALISA PENDIRIAN BISNIS SURAT KABAR - Taufik Dwi Laksono (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2007)
AbstractÂ Global economic crisis is which knock over do not only just state Indonesian but also almost the totality state in world cause the happening of relation disconnection work by on a large scale. A lot of company nor industry which close because unable to face the this crisis punching. at situation of like this governmental is not hold peace, not yet this old is governmental of roll named by a creative industry utilize to sustain the economics Indonesian and anticipate the disconnection work the on a large scale. This creative industry considered to be by a real economics movement and cannot live. One other assumed by a creative industry is sub of sector of advertisement and publication and also printing office.Â Keyword : Newspaper, headline news, harian regional , Breaking News.